Epoch-incremental reinforcement learning algorithms - Zajdel, Roman (Zielona Góra: Uniwersytet Zielonogórski)
In this article, a new class of the epoch-incremental reinforcement learning algorithm is proposed. In the incremental mode, the fundamental TD(0) or TD([lambda]) algorithm is performed and an environment model is created. In the epoch mode, on the basis of the environment model, the distances of past-active states to the terminal state are computed. These distances and the reinforcement terminal state signal are used to improve the agent policy.
Keywords: reinforcement learning; epoch-incremental algorithm; grid world